Sobre o fluxo de saturação: conceituação, aplicação, determinação e variação - Luna, Marcelo dos Santos de (2003)
The saturation flow is the main parameter for operational evaluation of signalized intersections. However, it seems it is often misused in signal timing, either due to the application of foreign measurement methods, or because inadequate understanding and application. The objective of this work was: to explain and define saturation flow, to test the suitability ofthe traditional and most modern procedures of measurement, and to expose somemisconceptions and misuses of it. Analyzing the behavior of a group of two-lane signalized approaches, assumed as typical main streets of Fortaleza, it was possible to show that the methods of measurement proposed by HCM and ARRB are not equivalent. It was found that the HCM procedure does not follow a queue system’s discharge rateconcept, and that the HCM and ARRB procedures employ measurement simplifications that overestimate vehicular flow values. As part of the effort to address the problems found, a procedure was developed for what was considered an appropriate measurement of the saturation flow at the studied approaches, as well as a method for establishing the beginning position of the saturated flow regimeand the minimumqueue size to be used in this procedure. The determination process of these thresholds may be used for the establishment of a more general procedure to deal with approachesof diverse characteristics. The observed variation in saturation flow values, under similar physical and operational conditions, raises doubts on the applicability of empiricalformulae for saturation flow estimation, as well as on the “one-calibration-only” procedure utilized by the SCOOT system. The results show the need for the elaboration of a saturation flow measurement procedure capable of capturing local characteristics and relegate the empirical formulae methods to planning applications, since they are not capable of capturing specific operational characteristics.